Cosmetic Outcomes of Simple Pediatric Facial Lacerations Repaired With Skin Adhesive Compared With Skin Adhesive With Underlying Adhesive Strips: A Randomized Controlled Trial. Issue 10 (26th October 2022) - Munns, Erin; Kienstra, Andrew J.; Combs, Patrick D.; Gabriele, Giovanni; Wilkinson, Matthew
Abstract : Objectives: A randomized controlled trial was designed to compare 2 methods of repairing simple pediatric facial lacerations. We hypothesized that wounds repaired with skin adhesive and underlying adhesive strips compared with skin adhesive alone would be superior in regard to cosmetic outcome. Methods: Patients aged younger than 18 years presenting to the emergency department with simple facial lacerations requiring repair were eligible for enrollment. Patients were randomly assigned to repair with either skin adhesive alone or skin adhesive with underlying adhesive strips. Families were contacted by phone 1 week after enrollment to discuss short-term complications. The cosmetic appearance of photographs of the scars at 2 months was analyzed using a visual analog scale by a blinded pediatric emergency physician and pediatric plastic surgeon. Results: One hundred twenty patients were enrolled, with 92 returning for the 2-month follow-up. The visual analog scale scores for the skin adhesive with adhesive strips group were similar to the skin adhesive alone group (60 mm vs 58 mm, P = 0.540). Spearman ρ correlation coefficient between the raters was 0.669, indicating strong agreement. There was no significant difference in rates of return visits, wound dehiscence, or infection. The skin adhesive with adhesive strips group had a longer time to perform the repair (195 seconds vs 107 seconds, P < 0.001). Conclusions: Using adhesive strips to first approximate a wound before applying skin adhesive leads to a similar cosmetic outcome compared with simple facial lacerations repaired with skin adhesive alone. Although the study showed longer time to complete the repair, this approach may still be useful in settings where approximation is difficult to obtain manually.